Kajian Sirkulasi Ruang Luar Terhadap Aliran Angin Pada Permukiman Padat Taman Sari Kota Bandung - Syafrina, Andina; Felly, Rizka (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2023)
Unplanned dense settlements in the development pay little attention to the technical aspects of the building and the environment, one of which is high humidity conditions and circulation pathways. Circulation in settlements can also function as wind circulation, which can affect natural ventilation, comfort, and the health of residents. This study uses a quantitative method with a descriptive approach to describe the relationship between the circulation width variable and the wind speed variable. The results of periodic field observations and measurements are then interpreted descriptively to determine the effect of circulation width on wind flow in densely populated settlements in Taman Sari, Bandung. The results showed that outdoor circulation close to open spaces had better wind speeds compared to areas far from open spaces.